Optimal access for Achilles Tendon Repair - D. A. Kisel'; A. M. Fayn; K. V. Svetlov; A. P. Vlasov; M. P. Lazarev; R. N. Akimov; I. G. Chemyanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Background. Despite the many accesses described in the literature for open Achilles tendon repair, there is no evidence of the benefits of this or that access confirmed by clinical observations.The aim is to determine and justify optimal access during open Achilles tendon repair.Material and methods. The article shows the result of the analysis of data from a literary search, experimental work on 12 lower limbs of 6 cadavers, a clinical study based on a retro-prospective analysis of the treatment of 128 people in the Department of Emergency Traumatology N.V. Sklifosovsky Research Institute from 2014 to 2022. The comparison group retrospectively included 47 patients (36.7%) with Achilles tendon injury, who underwent suture of the Achilles tendon from S and Z–shaped accesses from 2014 to 2017. The main group prospectively included 81 patients (63.3%) for 2018-2022, who underwent paramedial tendon access.Results. The analysis of a retrospective study showed that 3 patients from the comparison group with Achilles tendon injury in the postoperative period had ischemia of the wound edges with subsequent formation of necrosis and skin defect; 1 patient had a hypertrophic painful scar, which ulcerated from the constant traumatization of his shoe back (the total number of complications was 8.5%). In the patients of the main group, there were no complications in the postoperative period in any case. Conclusion. In our opinion, the paramedial tendon access is optimal, because there are no complications from the skin and leads to improved functional results.